A Study on Role of Women Entrepreneurship in Screw Pine Craft Thazhava, Kollam District, Kerala - Shiji T Vijay (International Journal of Advanced Science and Technology, 2020)
This study focussed into the Screw pine handicraft in Thazhava Village. Based on the State Government project of the Traditional craft preservation in Kerala. This program will help women to stay their own feet without depend on others. The screw pine mat making in Thazhava decreased due to several reasons. New generation women are not interested due to the low wages and suffering to prepare raw material making. A few years back, they started an SHG (Self Help Group) called “Mahima”, and they dropped later due to the financial hardship. The project aims to preserve traditional crafts through the Rural Art Hub Project formulated by Government of Kerala. The government-appointed ULCCS Ltd (Uralungal Labour Contract Co-operative Society Ltd) as a nodal agency and they hired Sargalaya to provide Sales, training, and development of the product.